Mutated Adenovirus Attacks in West Bengal, India: Risk Evaluation of Multi‐Country Outbreaks and Mitigation Strategies - Md. Ashrafur Rahman; Sydney Cronmiller; Julianne Ernest; Jonah Nguyen; Donovan Zong; Rob Davis; Amanda Rawa; Marie Roke Thomas; Rana Al Mosharrafa; Yeasna Shanjana; Md. Rabiul Islam (Nursing Open)
ABSTRACT Aim The human adenovirus (HAdV) is beginning to spread rapidly in children through human, surface and animal vectors. Around 12,000 cases were recognised in 2022 in West Bengal and a shocking number of cases arose throughout India and in other under‐developed areas. This is going to be a big threat to public health since no vaccine, awareness or protocol policies were introduced. Early detection, immediate isolation and proper policy developments are the key factors in overcoming the situation. Therefore, we performed this rapid review and discussed probable mitigation strategies, updated research on vaccine development, and treatment strategies to control the outbreaks of mutated HAdV. Design This is a narrative review of publicly available information. Methods Here, we extracted updated information and data using the terms HAdV outbreaks, mutations, species, risks and prevention from Google Scholar and PubMed. We considered relevant articles that have discussed prevention strategies, ongoing research, and antiviral drugs for managing HAdV outbreaks. Results Early detection from throat swabs, isolation and symptomatic treatments are required to minimise viral infections. A massive test needs to be performed to find the affected people. The cases should be immediately isolated. It is recommended to treat high‐touch surfaces with heat‐ or bleach‐containing cleaners to prevent the spread of infection. Oxygen support and many broad‐spectrum antivirals have been used to treat HAdV. Several studies showed antibody neutralisation and interactions between the natural killer cell receptor KIR3DS1 and HLA‐F in infected cells, indicating possible therapeutic options in the future. HAdV‐4 and HAdV‐7 vaccines have been limitedly approved for administration to military personnel. Conclusion Isolation, certain safety measures, broad‐spectrum antiviral drugs and further research on new vaccines could be useful to prevent this virus from producing a worldwide pandemic. Also, the authorities should ensure the proper therapeutic interventions and nursing care facilities for the infected children. Patient or Public Contribution Patient or public contribution was not relevant to our work.